Assessment of Serum Neutrophil Gelatinase Associated Lipocalin (NGAL) levels in patients of Systemic Lupus Erythematosus (SLE) with and without Lupus Nephritis (LN) - Ghaniya Ali, Nadeem Afzal, Muhammad Naim Ashraf, Fatima Saeed, Firdous Iqbal, Ayesha Muazzam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Lupus nephritis (LN) can occur as a complication of SLE causing further distress to patient. NGAL levels can help in foreseeing kidney injury in such afflicted. Thus, the study aimed to estimate serum NGAL levels in SLE patients with and without Lupus Nephritis. Methods: A cross sectional study was conducted at immunology Department, University of Health Sciences (UHS) Lahore. Purposive sampling technique was used to collect samples of patients diagnosed with SLE with and without Lupus Nephritis LN. Results: Study showed statistically significant results (p=0.00) with mean ±SD value of NGAL measured in patients of SLE with LN & without Lupus Nephritis LN. Conclusion: The study indicated that NGAL level was observed to be significantly raised in the patients of SLE with lupus nephritis as compare to the patients of SLE without lupus nephritis. Keywords: Acute kidney injury, Anti-double stranded DNA antibody, Chronic kidney disease, Lupus nephritis